2011
DOI: 10.3762/bjnano.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Self-organizing bioinspired oligothiophene–oligopeptide hybrids

Abstract: SummaryIn this minireview, we survey recent advances in the synthesis, characterization, and modeling of new oligothiophene–oligopeptide hybrids capable of forming nanostructured fibrillar aggregates in solution and on solid substrates. Compounds of this class are promising for applications because their self-assembly and stimuli-responsive properties, provided by the peptide moieties combined with the semiconducting properties of the thiophene blocks, can result in novel opportunities for the design of advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the present study, we designed a new family of guanine derivatives, 1 , 2a , 2b , 3a and 3b , containing an N -9 alkyl chain and attached via wedge-shaped oligothiophenes at the C-8 position ( Scheme 2 ). Oligothiophenes incorporating oligopeptide 53 , 54 or nucleobase 55 , 56 moieties have previously been explored for their self-assembly properties. Inspired by these studies, we envisioned that the π-conjugation between oligothiophenes and guanine moieties could lead to the induction of liquid crystallinity with a wide temperature range and charge transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we designed a new family of guanine derivatives, 1 , 2a , 2b , 3a and 3b , containing an N -9 alkyl chain and attached via wedge-shaped oligothiophenes at the C-8 position ( Scheme 2 ). Oligothiophenes incorporating oligopeptide 53 , 54 or nucleobase 55 , 56 moieties have previously been explored for their self-assembly properties. Inspired by these studies, we envisioned that the π-conjugation between oligothiophenes and guanine moieties could lead to the induction of liquid crystallinity with a wide temperature range and charge transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…[39,40] It should be noted that QTDA showed a much larger redshift compared with that of QT, which indicates that the assembly of QT and QTDA should be quite different. [9][10][11][12][13][14][15][16][17][18][19][20][21] It would be interesting to investigate whether such chirality transfer could be realized by weak interactions between a chiral oligopeptide and the achiral oligothiophenes. [9] It is known that when chiral peptide segments are covalently attached to achiral p-conjugated systems, the chirality will be transferred to the conjugated oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Oligopeptides are one of the most attractive biomolecules to adjust the stacking mode of p-conjugated oligomers because of their structural variation and their ability to form various secondary structures, such as a-helices and b-sheets. [9][10][11][12][13][14] These moieties have been covalently linked to oligopeptides and their assembly behavior and the corresponding properties were investigated. [9][10][11][12][13][14] These moieties have been covalently linked to oligopeptides and their assembly behavior and the corresponding properties were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, oligopeptides may serve as the supramolecular scaffold to guide the one-dimensional aggregation of the π-conjugated segments. A variety of different π-conjugated molecules, such as oligothiophenes, [112][113][114][115][116][117][118][119][120] naphthalenes, [121] anthracenes, [122] porphyrins, [123] phenylene vinylenes, [124] as well as perylene diimides [125] have been combined with oligopeptides to produce 1D semiconducting nanostructures. Meijer et al demonstrated that oligo(pheneylene vinylene) derivatives equipped with β-sheet-forming GAGAG oligopeptides formed aggregates in different solvents.…”
Section: To Wards Multiple-helical π-Conjugated Polymersmentioning
confidence: 99%
“…[124] Bäuerle et al synthesized oligothiophenes equipped with oligopeptide-PEO segments that self-assembled into well-defined left-handed helical nanofibrils with lengths of up to 2 µm, widths of 8 nm, and heights of 3 nm. [112][113][114][115][116] Tovar et al used oligopeptides inspired by the amyloid assembly paradigm to selfassemble oligothiophenes into one-dimensional nanostructures in aqueous media and used shear forces during injecting the quaterthiophene-oligopeptide hydrogels into a salt solution to produce macroscopically aligned fibrils of the oligothiophene derivatives. [117][118][119] The authors performed electric transport measurements on the ob-tained films and claimed hole mobilities of up to 0.03 cm 2 V −1 s -1 .…”
Section: To Wards Multiple-helical π-Conjugated Polymersmentioning
confidence: 99%